2000
DOI: 10.3354/meps203301
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic rates of swimming Humboldt penguins

Abstract: . Birds feeding chicks need to balance the costs of either (1) returning to the breeding island for the night and travelling back to the feeding grounds in the morning or (2) incurring increased thermoregulatory costs associated with resting at sea overnight. Simple calculations show that at water temperatures of 19°C we expect Humboldt penguins to show a tendency to remain at sea overnight if foraging areas are > 4 km from their island. In colder waters (12°C), this distance increases to > 9 km. Using previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 24 publications
1
23
0
1
Order By: Relevance
“…Pygoscelid penguins swimming horizontally chose to swim at speeds near their minimum COT , whereas spheniscid penguins and cormorants chose to swim at speeds below their minimum COT (Schmid et al, 1995;Luna-Jorquera and Culik, 2000). In LIPE swimming horizontally, COT decreased with increasing speed and seemed to approach a minimum at 1.8·m·s -1 (Bethge et al, 1997); our LIPE swam at 1.8-1.9·m·s -1 .…”
Section: Speed Change With Depth and Its Regulationmentioning
confidence: 69%
“…Pygoscelid penguins swimming horizontally chose to swim at speeds near their minimum COT , whereas spheniscid penguins and cormorants chose to swim at speeds below their minimum COT (Schmid et al, 1995;Luna-Jorquera and Culik, 2000). In LIPE swimming horizontally, COT decreased with increasing speed and seemed to approach a minimum at 1.8·m·s -1 (Bethge et al, 1997); our LIPE swam at 1.8-1.9·m·s -1 .…”
Section: Speed Change With Depth and Its Regulationmentioning
confidence: 69%
“…We converted ODBA values from Magellanic penguins into power, assuming a linear relationship between ODBA and metabolic power , Fahlman et al 2008, Halsey et al 2008, Green et al 2009), and by using data from Luna-Jorquera & Culik (2000). These latter authors reported the relationship between mass-specific metabolic power and swim speed for congeneric Humboldt penguins Spheniscus humboldti swimming underwater in a still-water swim channel.…”
Section: Methodsmentioning
confidence: 99%
“…This can be determined using data in the literature on oxygen consumption in penguins swimming at known speeds horizontally in swim channels (though typically at depths of <1m) because 1ml of oxygen is the substrate responsible for yielding ~20J of energy (Stahel and Nicol, 1987). Here, the power output of swimming at particular speeds from Eqn6 can be regressed against the known power input derived from oxygen consumption measurements made on the congeneric Humboldt penguin (Spheniscus humboldti) (Luna-Jorquera and Culik, 2000). The polynomial fit describing this gives:…”
Section: Descent Phasementioning
confidence: 99%
“…Here, oxygen use equates linearly with energy expenditure (Stahel and Nicol, 1987). In addition, there are good quality data on energy expenditure in penguins (Bethge et al, 1997;Culik et al, 1996;Culik et al, 1994;Luna-Jorquera and Culik, 2000) that lend credibility to the modelling exercise.…”
Section: Introductionmentioning
confidence: 99%